Critical Essay: Reconsidering critical performativity - Cabantous, Laure; Gond, Jean-Pascal; Harding, Nancy; Learmonth, Mark (Human relations (New York), 2016)
In recent years, we have witnessed the emergence of ‘critical performativity’, a concept designed to debate relationships between theory and practice and encourage practical interventions in organizational life. Notwithstanding its laudable ambition to stimulate discussion about engagement between critical management studies researchers and practitioners, we are concerned that critical performativity theory is flawed as it misreads foundational performativity authors, such as Austin and Butler, in ways that nullify their political potential, and ignores a range of other influential theories of performativity. It also overlooks the materiality of performativity. We review these limitations and then use three illustrations to sketch out a possible alternative conceptualization of performativity. This alternative approach, which builds on Butler’s and Callon’s work on performativity, recognizes that performativity is about the constitution of subjects, is an inherently material and discursive construct, and happens through the political engineering of sociomaterial agencements. We argue that such an approach – a political theory of organizational performativity – is more likely to deliver on both theoretical and practical fronts than the concept of critical performativity.